PERAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT DALAM PEMBANGUNAN EKONOMI DI INDONESIA (STUDI KASUS NOMOR: 1/PDT.SUS-KPPU/2021/PN.NIAGA.JKT.PST) - Natasha Marcella Geovanny; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
This research was conducted with the aim of providing an overview of the role of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition in economic development in Indonesia. The research method used in this study is a normative juridical method. The results in this study indicate that the role of law in an economic development is something that is very important and its existence cannot be ignored. So that it can be concluded that, if the legal conditions in a country run well, then economic development will also be easy to implement. However, if the applicable law in a country cannot be implemented effectively, it will also have a negative impact on the process of economic development in that country. Therefore, in order to realize a good legal process and economic development, good synergy is needed from legal substance, legal structure, and also legal culture or culture in carrying out law in a country so that law can work properly.